Time-loss injuries and illnesses at the FIFA world cup Qatar 2022 - Serner, A.; Chamari, K.; Hassanmirzaei, B.; Moreira, F.; Bahr, R.; Massey, A.; Grimm, K.; Clasren, B.; Tabben, M. (Science and Medicine in Football, 2025)
The study aimed to analyse incidence and characteristics of time-loss injuries and illnesses during the FIFA World Cup Qatar 2022. Of 838 male football players, 705 consented to participate. Team medical staff reported 82 time-loss injuries, corresponding to an injury event incidence of 5.6 injuries/1000 h of total exposure (95%CI 4.5 to 7.0 injuries/1000 h), with a median of 2 time-loss injury events per team (IQR, 1 to 4.5, range 0-7). The total injury burden was 103 (95% CI 61 to 152) days per 1000 h. Muscle/tendon injuries had the highest incidence of tissue types (48 cases, 3.3/1000 h (95% CI 2.5 to 4.4), and hamstring muscle injuries were the most frequent diagnosis (16 cases, incidence 1.1/1000 h, 95% CI 0.6 to 1.8). Match injury event incidence was 20.6/1000 h (15.0 to 27.7) and training injury event incidence was 2.1/1000 h (1.4 to 3.1). The majority (52%) of sudden-onset injuries were non-contact injuries, 40% direct contact and 8% indirect contact. We recorded 15 time-loss illnesses, corresponding to an illness event incidence of 1.1 per 1000 competition days, (95% CI: 0.6 to 1.8), and illness burden of 2.1 (1.0 to 3.4) days lost per 1000 competition days. The most common illness was respiratory infection (12 cases, 80%). Match injury event incidence was the lowest in any FIFA World Cup since injuries have been monitored.